Services offered by Balay Ilonggo an assessment - Castillo, Yvette Marie G.; Catalan, Leah E.; Dayot, Chicklette D.; Duran, Chelito E.; De los Reyes, Kharla D.
Executive summary-dormitories are considered the second home of students who do not live in their own houses. Balay Ilonggo is the lone dormitory in UPV Iloilo City Campus that addresses the housing needs of UP students and constituents. This study assessed the services offered by Balay Ilonggo both to the transient guests and dormers and formulated suggestions and recommendations for improvements that can be used by the Balay Ilonggo management and UPV Administration in improving the said services. Information and data gathering were limited to the second semester of Academic Year 2001-2002. The researcher identified variables in determining what factors affect the preferences of the guests and dormers. Relationships among these variables were established by the researchers and used in the overall analysis. The results of the study showed that transients' preference are directly affected by support services offered by Balay Ilonggo. They also demand better accommodation, good management and staff, and are most critical of the facilities, particularly the bathrooms and bedrooms. On the other hand, the dorm residents consider the rates in Balay Ilonggo as the major influencing factor, followed by the treatment of management and staff and the facilities offered. Several suggestions of the respondents were enumerated. In implementing these suggestions and recommendations, the management should weigh the cost against the benefits that will be derived.